Handbook of Hydrogen Storage 2010
DOI: 10.1002/9783527629800.ch2
|View full text |Cite
|
Sign up to set email alerts
|

Physisorption in Porous Materials

Abstract: Physisorption or physical adsorption is the mechanism by which hydrogen is stored in the molecular form, that is, without dissociating, on the surface of a solid material. Responsible for the molecular adsorption of H 2 are weak dispersive forces, called van der Waals forces, between the gas molecules and the atoms on the surface of the solid. These intermolecular forces derive from the interaction between temporary dipoles which are formed due to the fluctuations in the charge distribution in molecules and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…Of particular interest are dihydrogen and carbon dioxide, because of their environmental and economic importance. Dihydrogen is considered to be the most promising energy carrier for the substitution of fast diminishing liquid fuel resources in mobile applications . In particular, H 2 is a fully renewable energy source, environmentally friendly, nontoxic, and suitable as an automobile fuel.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest are dihydrogen and carbon dioxide, because of their environmental and economic importance. Dihydrogen is considered to be the most promising energy carrier for the substitution of fast diminishing liquid fuel resources in mobile applications . In particular, H 2 is a fully renewable energy source, environmentally friendly, nontoxic, and suitable as an automobile fuel.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the storage capacity, the incorporation of strong adsorption sites (for example open metal sites) is considered as one of the promising strategies . Also reduced pore size was found to have positive effects on the density of stored gas . Calculations based on carbon materials showed that slit pores with a width of 6 Å should have the highest hydrogen uptake at very low pressures because they exhibit the strongest interaction potential .…”
Section: Results and Disscusionmentioning
confidence: 99%
“…In both the gaseous and liquid forms, hydrogen preserves its molecular structure. A further method to store hydrogen in molecular form is the physisorption on large-surface-area materials at cryogenic temperatures [11]. This storage method takes advantage of the dipolar interactions occurring between the hydrogen molecules and the surface of the absorbent material.…”
Section: Hydrogen Storage and Applicationsmentioning
confidence: 99%